Action Plan for Gender, Diversity and Inclusion in CGIAR’s Workplaces: Principles, Key Objectives, Performance Benchmarks and Targets - CGIAR System Organization (CGIAR System Organization, 2020)
This document sets forth an action plan (“Action Plan”) in support of the implementation of the Framework for Gender, Diversity and Inclusion in CGIAR’s Workplaces (“Framework”) over the 2-year period 2020 – 2021. This Action Plan is ambitious and substantial, and demonstrates the CGIAR System’s significant shared commitment to advancing gender, diversity and inclusion (GDI) in CGIAR’s workplaces.